46 Reflections on overdetection: longitudinal qualitative follow-up within a mammography decision aid trial. (4th December 2019) - Hersch, Jolyn; Jansen, Jesse; Barratt, Alexandra; Dhillon, Haryana; Houssami, Nehmat; Jacklyn, Gemma; Irwig, Les; McGeechan, Kevin; McCaffery, Kirsten
Abstract : Objectives: Supporting women to make well-informed decisions about breast cancer screening requires effective communication about possible outcomes including overdetection or overdiagnosis. We conducted a qualitative sub-study within a randomised controlled trial to investigate the effects, over 2 years of follow-up, of providing information about overdetection to women considering breast screening. Method: Participants recruited to the RCT were women aged 48–50, without a personal or strong family history of breast cancer, who had not undergone mammography in the past 2 years. We randomised women to receive the intervention decision aid (evidence-based information on overdetection, breast cancer mortality reduction, and false positives) or a control decision aid (identical but without overdetection information). We conducted semi-structured qualitative interviews with a random sub-sample of trial participants after 2–3 months (n=50 including both study groups) and re-interviewed them at 1 year (n=45) and 2 years (n=38). Interviews were audio-recorded, transcribed, and analysed thematically using framework analysis. Results: Women's initial responses to learning about the risk of overdetection varied, as did their evaluations of the trade-off between benefits and harms of screening. For some, the new information was disturbing and led them to question the value of screening, while others were unconcerned. Over time, we explored the evolution of women's perspectives as their impressions of the study decision aids interacted with the influences of screening program invitations, doctors and peers, and personal risk perceptions. Many women ultimately decided they would prefer to undergo screening, despite acknowledging the risk of overdetection, because of other factors they considered more important. Most women favoured presenting balanced information about screening (including harms) to encourage informed decision making. Discussion: This longitudinal qualitative study, embedded within a randomised controlled trial, has provided a unique opportunity to examine in depth the trajectories of women's thoughts and feelings about breast screening over the course of 2 years of follow-up after a decision support intervention.